Effectiveness of PhET Simulation in Acid–Base Practicum for Maritime Engineering Students: Alignment with IMO Model Course 7.04 - Khoirotun Nafillah; Helena Devi Ariyani; Kirtyana Nindita; Fajar Sari Kurniawan; Ahmad Umam Aufi (Jurnal Inovasi Pembelajaran Kimia, 2026)
This study aims to examine the effectiveness of PhET Simulation in acid–base practicums for maritime engineering students. The study addresses common challenges in basic chemistry practicums, including limited laboratory facilities, restricted practicum time, and students’ low conceptual understanding. As a novel contribution, this study provides empirical evidence on the use of interactive virtual simulations in the context of maritime vocational education aligned with IMO Model Course 7.04. A pre-experimental one-group pretest–posttest design was employed involving 72 first-semester students. Data were collected using a validated and reliable multiplechoice test and analyzed using non-parametric statistical methods. The results indicate a significant improvement in students’ learning outcomes after the implementation of PhET Simulation. These findings suggest that virtual laboratory simulations are an effective alternative to support conceptual understanding in acid–base learning. Furthermore, this study highlights the potential of integrating digital simulation tools into maritime chemistry education to support competency standards outlined in IMO Model Course 7.04.